Protective and Detoxifying Enzyme Activity and ABCG Subfamily Gene Expression in Sogatella furcifera Under Insecticide Stress - Zhou, Cao; Yang, Hong; Wang, Zhao; Long, Gui-Yun; Jin, Dao-Chao (Frontiers in Physiology, 2019)
Sogatella furcifera, an important migratory pest of rice, has substantial detrimental effects on rice production. To clarify the mechanism whereby S. furcifera responds to insecticide stress, we measured the activity of its protective [superoxide dismutase (SOD); peroxidase (POD); catalase (CAT)] and detoxifying [carboxylesterase (CarE); glutathione S-transferase (GST); mixed-function oxidase (MFO)] enzymes and the expression levels of its ATP-binding cassette subfamily G (ABCG) transporter genes in response to sublethal concentrations (LC10 and LC25) of the insecticides thiamethoxam, buprofezin, and abamectin. On the bases of the transcriptome data and the ABCG genes of Laodelphax striatellus, we obtained 14 full-length ABCG sequences for S. furcifera. RT-qPCR results showed that 13, 12, and 9 sfABCG genes were upregulated in the presence of thiamethoxam, buprofezin, and abamectin, respectively, at LC10. Moreover, 13 and 7 sfABCG genes were upregulated following treatment with thiamethoxam and abamectin, respectively, at LC25. Enzyme activity assays showed that although thiamethoxam, buprofezin, and abamectin induced GST, CarE, CAT, POD, and SOD activity, they did so at different concentrations and exposure times. The activity of MFO was generally inhibited with prolonged exposure to the three insecticides, with the inhibitory effect being most significant at 72 h. These results indicate that S. furcifera differs in its response to different types or concentrations of insecticides. Taken together, our results lay the foundations for gaining a deeper understanding of the mechanisms underlying the adaptation of S. furcifera to different types of insecticides, which would be of considerable significance for the development of effective pest management strategies.